Honesty pledges for the behaviorally-based regulation of dishonesty. Issue 5 (4th May 2021) - Peer, Eyal; Feldman, Yuval
ABSTRACT: A common regulatory dilemma is determining how much trust authorities can place in people's self-reports, especially in contexts with an incentive to cheat. In such contexts, regulators are typically risk averse and do not readily confer trust, resulting in excessive requirements when applying for permits, licenses, etc. Studies in behavioral ethics have suggested that asking people to ex-ante pledge to behave ethically can reduce their level of dishonesty and noncompliance. However, pledges might also backfire by allowing more people to cheat with no real sanctions. Additionally, pledges' effects have almost always been studied in one-shot decision making without sanctions. We explore pledges' potential effects by manipulating whether pledges were accompanied by sanctions (fines) and testing their impact on sequential, repeated ethical decisions. We find that pledges can considerably and consistently reduce dishonesty, and this effect is not crowded out by the presence of fines. Furthermore, pledges also affect "brazen liars" who cheat to a large extent and also those who score low on tendency to follow rules and norms. We conclude that pledges could be an effective tool for the behavioral regulation of dishonesty, to reduce regulatory burden, and to build a more trusting relationship between government and the public.